Results of the Primary Evaluation of Processes of Natural Self-cleaning of Lake Yanisyarvi As an Object of Fishing Value - Kuchko, Alexander; Sidorova, Natalya; Mamontova, Olga (KnE Life Sciences, 2020)
The initial assessment of the processes of natural self-cleaning of the lakes of the Yanisyarvi basin was carried out. The morphological, physiological and biochemical characteristics of aquatic microflora were used as the main indicators of natural self-cleaning processes in the eco-system. The dominance of the anaerobic phase of self-purification due to the enzymatic activity of obligate and facultative anaerobes was described. The proportion of anaerobes controlling intra-water geochemical processes averaged 90%, and aerobes - 10%. The morphological component was represented by a wide variety, the presence of all morphotypes with the exception of crimped forms was noted. The study of tinctorial traits, isolated isolates made it possible to establish the predominance of representatives of the Gracilicutes department, whose number, depending on the sampling station, varied from 55 to 95%. The biochemical component of the study was performed on the basis of determining the activity of isolates in 8 groups of enzymes.